PENGGUNAAN Metarhizium anisopliae SOROKIN LOKAL TERHADAP Spodoptera frugiperda J.E. SMITH - Desita Salbiah; Siska Fronika (DINAMIKA PERTANIAN, 2021)
The main pest that attacks sweet corn crops is the armyworm Spodoptera frugiperda J.E. Smith. The armyworm S. frugiperda is harmful to sweet corn crops with an attack rate of 15-100%. Control of armyworm S. frugiperda in sweet corn plants generally still uses synthetic chemical insecticides because they can control pests quickly and practically. Biological control is an alternative method that can be used to overcome the impacts caused by the use of synthetic insecticides. The biological agent that has the potential to control plant pests is the entomopathogenic fungi Metarhizium anisopliae (Metsch) Sorokin. The purpose of this research is to obtain the concentration of the local entomopathogenic fungi Metarhizium anisopliae (Metsch) Sorokin which is able to control the armyworm Spodoptera frugiperda J. E. Smith. The research was conducted at the Laboratory of Plant Pests, Faculty of Agriculture, Riau University from June to August 2020. The research was designed a completely randomized design with six treatments local entomopathogenic fungi concentrations M. anisopliae 0 g.l-1 water, 10 g.l-1 water, 20 g.l-1 water, 30 g.l-1 water, 40 g.l-1 water, 50 g.l-1 water, and four replications, to obtain 24 experimental units. The results showed that the use of the entomopathogenic fungi M. anisopliae (Metsch) Local Sorokin with a concentration of 30 g.l-1 water contains a conidia density 0.65 x 108 con.ml-1 is a concentration capable of controlling the armyworm S. frugiperda with total mortality of 82,50%.